The Impact of Students' Cumulative Achievement Index and Their Drive to Choose A Study Program UHAMKA’s PGSD - Aulia, Firda; Murwitaningsih, Susanti (Jurnal Paedagogy, 2022)
This study aims to examine the impact of study program motivation on the overall performance index of students enrolled in UHAMKA PGSD. All 485 students from the PGSD at the UHAMKA’s batch of 2018 made up the study's sample. This study used the associative method along with a quantitative approach. With a total sample of 90 students, sampling was done using the Simple Random Sampling approach. A questionnaire and documentation were the study's tools. Before the instrument was utilized in the study, validity and reliability tests were performed to assess the instrument's quality. A straightforward regression analysis was used to examine the research data. The results had a sign value of 0.002 0.05, indicating that the alternative hypothesis (Ha) had been accepted and the null hypothesis (Ho) had been rejected. Therefore, the analysis in this study's conclusion is that there is a significant relationship between the desire to select a study program and the overall achievement index of the UHAMKA class of 2018, with a coefficient of determination (adjusted R square) of 10.3%.